Nicotine Enhances Goal-Tracking in Ethanol and Food Pavlovian Conditioned Approach Paradigms - Angelyn, Hailley; Loney, Gregory C.; Meyer, Paul J. (Frontiers in Neuroscience, 2021)
Rationale Nicotine promotes alcohol intake through pharmacological and behavioral interactions. As an example of the latter, nicotine can facilitate approach toward food- and alcohol-associated stimuli (“sign-tracking”) in lever-Pavlovian conditioned approach (PavCA) paradigms. However, we recently reported that nicotine can also enhance approach toward locations of reward delivery (“goal-tracking”) triggered by ethanol-predictive stimuli when the location of ethanol delivery is non-static (i.e., a retractable sipper bottle). Objective To determine whether the non-static nature of the reward location could have biased the development of goal-tracking in our previous study (Loney et al., 2019); we assessed the effect of nicotine in a lever-PavCA paradigm wherein the location of ethanol delivery was static (i.e., a stationary liquid receptacle). Then, to determine whether nicotine’s enhancement of goal-tracking is unique to ethanol-predictive stimuli, we assessed the effect of systemic nicotine on approach triggered by food-predictive stimuli in a lever-PavCA paradigm. Methods Long–Evans rats were used in two PavCA experiments wherein a lever predicted the receipt of ethanol (15% vol/vol; experiment 1) or food (experiment 2) into a stationary receptacle. Prior to testing, rats were administered nicotine (0.4 mg/kg subcutaneously) or saline systemically. Results In both experiments, nicotine increased measures of goal-tracking, but not sign-tracking. Conclusion Nicotine can facilitate approach to reward locations without facilitating approach to reward-predictive stimuli. As such, conceptualization of the mechanisms by which nicotine affects behavior must be expanded to explain an enhancement of goal-tracking by nicotine.